Biodiesel production by valorizing waste Phoenix dactylifera L. Kernel oil in the presence of synthesized heterogeneous metallic oxide catalyst (Mn@MgO-ZrO2). (1st January 2018) - Jamil, Farrukh; Al-Muhatseb, Ala'a H.; Myint, Myo Tay Zar; Al-Hinai, Mohab; Al-Haj, Lamya; Baawain, Mahad; Al-Abri, Mohammed; Kumar, Gopalakrishnan; Atabani, A.E.
Graphical abstract: Highlights: Valorization of abundantly available Phoenix dactylifera L. waste biomass. Synthesis of new metal oxide catalyst with balanced acidic and basic active sites. Synthesized catalyst possesses enough pore size >5 to support transesterification. Catalyst proved its effectiveness by giving biodiesel yield up to 96.4%. Biodiesel characterization revealed the effectiveness of the synthesized catalyst. Abstract: The present study intended to produce biodiesel as an efficient fuel from waste Phoenix dactylifera L. kernel oil in the presence of synthesized efficient heterogeneous metallic oxide catalyst (Mn@MgO-ZrO2 ). The performance of synthesized metallic oxide catalyst was evaluated based on biodiesel yield and the process has been optimized. The optimum biodiesel yield was 96.4%, when process temperature was 90 °C, catalyst loading 3 wt%, methanol to oil ratio 15:1 and reaction duration was 4 h. The product biodiesel was characterized in order to evaluate its quality according to ASTM and EN standards. Thus, characterization of biodiesel revealed that it fulfills the standard ranges defined by ASTM and EN: its acid value was 0.11 mg KOH/g, density 881 kg/m 3, viscosity 3.85 mm 2 /s, flash point 142 °C and suitable low-temperature properties. It can thus be concluded that synthesized heterogeneous catalyst can be used efficiently for biodiesel production from waste Phoenix dactylifera L. kernel oil which satisfied the international standards defined by ASTM and EN.